2018
DOI: 10.1177/2040620718774258
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-based prediction of real-life dosing of extended half-life clotting factor concentrates on hemophilia

Abstract: The improvement of clotting factor concentrates (CFCs) has undergone an impressive boost during the last six years. Since 2010, several new recombinant factor (rF)VIII/IX concentrates entered phase I/II/III clinical trials. The improvements are related to the culture of human embryonic kidney (HEK) cells, post-translational glycosylation, PEGylation, and co-expression of the fragment crystallizable (Fc) region of immunoglobulin (Ig)G1 or albumin genes in the manufacturing procedures. The extended half-life (EH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…As patients present with varied clinical phenotypes, tailored patient therapy should be guided by careful consideration of the overall improved PK profile of an EHL rFVIII product [24,30]. Besides half-life, PK parameters such as AUC, CL, and time above FVIII threshold level are important contributors to protection from bleeds and, thus, are of clinical significance [31]. In patients with severe hemophilia A, time spent with very low FVIII levels potentially carries the risk of spontaneous joint bleeds [3].…”
Section: Discussionmentioning
confidence: 99%
“…As patients present with varied clinical phenotypes, tailored patient therapy should be guided by careful consideration of the overall improved PK profile of an EHL rFVIII product [24,30]. Besides half-life, PK parameters such as AUC, CL, and time above FVIII threshold level are important contributors to protection from bleeds and, thus, are of clinical significance [31]. In patients with severe hemophilia A, time spent with very low FVIII levels potentially carries the risk of spontaneous joint bleeds [3].…”
Section: Discussionmentioning
confidence: 99%
“…Because coagulation factor trough values are generally used for the management of hemophilia, 8,14‐16 we also developed an indirect method to project the factor IX trough value(s). In our analysis we used AUC as an intermediate step for prediction of factor IX trough values because we found that AUC has strong statistical relationships with both the concentration at 24 hours and trough values (Table 1 and Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…For coagulation factors, a trough level above 1 IU/dL is often considered clinically relevant for the prevention of bleeding in patients with hemophilia 8,14‐16 . Because there is no established target FIX AUC level that corresponds to trough level, we define target AUC as the minimum AUC value that corresponds with FIX trough level ≥ 1 IU/dL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of clearance as a key parameter for selecting appropriate dosing regimen and therapeutic individualization is now being appreciated in haemophilia research community. 3,13 Currently, limited PK studies are submitted for licensing of biological products used for rare coagulation disorders. For example, the FDA package insert for COAGADEX (Coagulation Factor X) provides clearance data only for >12 years old subjects.…”
Section: Igg Product and Age Categorymentioning
confidence: 99%